PKM PERSIAPAN EKSPOR PUPUK ORGANIK KE MOZAMBIQUE: MENGHADAPI HAMBATAN TARIF DAN KESIAPAN PRODUK (STUDI KASUS PADA PT. SOLUSI TANI MAKMUR, KOTA BANDUNG) - Hasan, Zidny Ilma; Akbar, Adhadhian; Bustaman, Arief (LPPM Universitas Bina Bangsa, 2024)
PT. Solusi Tani Makmur faces several challenges in preparing for the export of organic fertilizer to Mozambique, primarily in understanding export regulations, meeting documentation requirements, securing safe payment methods, and protecting intellectual property rights. These challenges hinder the company’s readiness to leverage international market opportunities and benefit from the Indonesia-Mozambique Preferential Trade Agreement. This community engagement program aims to provide structured support to enhance PT. Solusi Tani Makmur's readiness to comply with export regulations and strengthen its competitiveness in the global market. The methods used in this program include direct consultation, business mentoring, and data analysis on regulations and target markets. Through these approaches, the company received guidance on verifying the legality of export procedures, preparing necessary documents, selecting secure payment methods, and coordinating with the Indonesian Embassy in Mozambique. The results indicate a significant improvement in PT. Solusi Tani Makmur’s readiness for export. Following the mentoring, the company successfully fulfilled export requirements and developed a more structured strategy for market expansion. This support has enhanced the company’s export capability, enabling more effective market penetration in Mozambique